Estimation of Demographic Parameters and Food Plant Species Composition of Long-Tailed Macaques in Semongkat Nature Park - Hidayati, Maulia; Syaputra, Maiser; Indrityatno, Indrityatno (Jurnal Biologi Tropis, 2025)
Indonesia is renowned for its rich biodiversity, encompassing a wide variety of flora and fauna, including primates such as the long-tailed macaque (Macaca fascicularis). This species exhibits high adaptability to environmental changes. Long-tailed macaques (Macaca fascicularis) in Indonesia show high adaptation to environmental changes, including behavioural changes due to human interactions. Fieldwork was conducted in September 2024, employing the line transect method for demographic estimation and plot sampling for vegetation analysis. Data analysis for demographics was quantitative and forage plant was deskriptive and quantitative. 61 long-tailed macaque individuals in total. Group sizes ranged from 17 to 25 individuals, with an overall population density of 1.52 individuals per hectare, a sex ratio of 1:0.75, a birth rate of 0.8, and a mortality rate ranging from 0.65 to 0.75. Age structure analysis indicates a progressive population trend. A total of 14 plant species were identified as food sources, with Importance Value Indices (IVI) ranging from 52.16% to 8.61% at the tree level, 35.22% to 10.29% at the pole level, 25% to 10% at the sapling level, and 20% to 10% at the seedling level. These findings suggest that the macaque population is demographically stable, yet increasingly reliant on anthropogenic food sources due to altered foraging behaviors.